Perkawinan Campuran , Pencatatan Keabsahan Pencatatan Perkawinan diluar Indonesia Berdasarkan Peraturan Perundang-Undangan - Sheanny Scolastika; Gavrilla Theodora; Olga Nadina; Tsamara Probo Ningrum (Fakultas Hukum, Universitas Warmadewa, 2020)
International marriage is a marriage with a foreign element in it. Mixed marriage as set out in article 57 of Law No. 1 of 1974 on Marriage states that mixed marriage is a marriage between two persons in Indonesia subject to different laws, due to differences in citizenship and one of the foreign nationals and one of the Indonesian nationals. Regulations on the registration of marriage outside Indonesia under the Population Administration Law and the registration of marriage outside Indonesia under the marriage law use the term â€œregistrationâ€ whereas the provisions of the Population Administration Act use the term â€œregistryâ€ so that further discussion of the distinction should be made. In addition to the timeframe there is also a difference, in the marriage law provides a 1 (one) year deadline, while in the Public Administration Act gives the registration deadline of only 1 (one) month. Based on this background the problem can be drawn first, in the event of a marriage outside Indonesia, which rule of law will apply. Second, is there a difference in meaning between